Mekanisme Penyederhanaan Birokrasi Melalui Penyetaraan dan Pengalihan Jabatan Administrasi Ke Dalam Jabatan Fungsional di Kabupaten Serang - Edah Jubaedah; Leo Agustino; Arenawati (JDKP Jurnal Desentralisasi dan Kebijakan Publik, 2023)
The simplification of the bureaucracy is part of the grand action plan for Indonesia's bureaucratic reform design towards a world-class government. In bureaucratic reform, there are eight areas of change, one of which contains the simplification of the bureaucracy, which is contained in the fulfillment area at the third point, namely structuring and strengthening the organization in which it mandates equalization and transfer of positions. The simplification of the bureaucracy is predicted to be able to accelerate services and realize good governance through effective and efficient governance. Too many levels of bureaucracy in structural positions that must be passed in service is one of the causes of the ineffectiveness of the existing bureaucracy. So that it encourages the government to issue policies through cutting echelonization into two levels by equalizing echelon IV positions and transferring administrative positions into functional positions. As a form of service that is simple but considered more effective and efficient in providing services as well as improving the work of ASN to be more performing. All central and regional agencies are required and guided to simplify the bureaucracy in order to realize the implementation of bureaucratic reform to realize effective and efficient governance by optimizing the use of an electronic-based government system. As a form of service that is simple but considered more effective and efficient in providing services as well as improving the work of ASN to be more performing. All central and regional agencies are required and guided to simplify the bureaucracy in order to realize the implementation of bureaucratic reform to realize effective and efficient governance by optimizing the use of an electronic-based government system. As a form of service that is simple but considered more effective and efficient in providing services as well as improving the work of ASN to be more performing. All central and regional agencies are required and guided to simplify the bureaucracy in order to realize the implementation of bureaucratic reform to realize effective and efficient governance by optimizing the use of an electronic-based government system.